2014
DOI: 10.1163/15685403-00003346
|View full text |Cite
|
Sign up to set email alerts
|

New methods for collecting Ostracoda (Crustacea) in stony sediments with methodological remarks on the separation of ostracods from sediment

Abstract: New methods for sampling ostracods are described specifically for hyporheic environments and coarse sediments (i.e., pebbles and rocks). The main module is a diaphragm pump that establishes an artificial current strong enough to force individuals from their habitat. Two other methods are presented for separating living ostracods from sediment samples taking advantage of their biological and physical properties: (1) emigration out of a basket; (2) harvesting ostracods floating on the water surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Besides, Külköylüoğlu (1999) collected species from February to November from springs of Nevada. Martín-Rubio et al (2005) reported species from Lake Caicedo de Yuso-Arreo (Spain) in January, February, March, April, June -August, and November when Scharf and Viehberg (2014) encountered species in February, April, June, July, September and October in Germany. The occurrence of the species in April from Lake Meyil (Konya, Turkey) (Akdemir 2008) and from May to January herein is now supported previously reported reproduction period of species.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Külköylüoğlu (1999) collected species from February to November from springs of Nevada. Martín-Rubio et al (2005) reported species from Lake Caicedo de Yuso-Arreo (Spain) in January, February, March, April, June -August, and November when Scharf and Viehberg (2014) encountered species in February, April, June, July, September and October in Germany. The occurrence of the species in April from Lake Meyil (Konya, Turkey) (Akdemir 2008) and from May to January herein is now supported previously reported reproduction period of species.…”
Section: Discussionmentioning
confidence: 99%